Location based security architecture evaluated using ATAM - Begum, Almas; Cyril Raj, V (International Journal of Engineering and Technology, 2018)
The usage of internet along with growing number of smart phones let public to access and store delicate data , Mobile banking, Contact lists, information on Location(EG: GPS), Etc. regularly.So it is becoming a challenging task to provide Security to smart phones for protecting data. The most important step in the early stage of software development is architecture representation and analysis.The objective of this paper is to propose an architecture for smart phones, represent using MVC model and evaluated using ATAMto extractsecurity quality attributes.ATAM list the quality attributes in the following categories that is Risk, Non-Risk, Tradeoff and sensitivity points.